Pengembangan Lembar Kerja Peserta Didik (LKPD) Bahasa Indonesia Kelas VIII SMP Berbasis Cooperative Learning pada Materi Menulis Naskah Drama - Trisman Harefa (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to develop Indonesian LKPD for class VIII SMP based on Cooperative Learning on the material "Writing Drama Scripts" which is suitable for use in the learning process. This type of research is a development research using the Hannafin and Peck model which consists of three stages, namely the needs assessment stage, design phase, and development and implementation phase. The instruments used in the assessment to determine the feasibility of LKPD are in the form of validation questionnaires for validators of material experts, linguists, and design experts as well as student response questionnaires. Data analysis was obtained by collecting quantitative and qualitative data from each validator, and students